2019
DOI: 10.1111/ppe.12570
|View full text |Cite
|
Sign up to set email alerts
|

Associations between estimated foetal weight discordance and clinical characteristics within dichorionic twins: The NICHD Fetal Growth Studies

Abstract: Background Birthweight discordance is well studied, with less known about longitudinal inter‐twin differences in foetal growth. Objective To examine inter‐twin per cent differences in EFW (EFW%), head (HC%) and abdominal circumference (AC%), and femur length (FL%) across gestation in dichorionic twin gestations and explore associated characteristics. Methods Foetal biometrics were assessed by ultrasound and EFW calculated at ≤6 study visits among women with dichorionic twin pregnancies enrolled in the NICHD Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…6 This study by Amyx et al found that maternal underweight and IVF were both associated with small for gestational age in twins. 4 Despite the evidence, there is much disagreement and controversy regarding the definition of what is reduced foetal growth among twins and whether twin-specific or singleton growth charts should be utilised to determine twin growth trajectory or define pathologic small size. 1 Twin charts are recommended by some, while others use singleton charts.…”
Section: Institute Of Child Health and Human Development (Nichd) Fetalmentioning
confidence: 99%
See 4 more Smart Citations
“…6 This study by Amyx et al found that maternal underweight and IVF were both associated with small for gestational age in twins. 4 Despite the evidence, there is much disagreement and controversy regarding the definition of what is reduced foetal growth among twins and whether twin-specific or singleton growth charts should be utilised to determine twin growth trajectory or define pathologic small size. 1 Twin charts are recommended by some, while others use singleton charts.…”
Section: Institute Of Child Health and Human Development (Nichd) Fetalmentioning
confidence: 99%
“…In this issue of Paediatric and Perinatal Epidemiology, Amyx and colleagues used data from the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Fetal Growth Study‐Twins to investigate inter‐twin differences in foetal growth by considering pre‐existing maternal factors that may alter growth trajectory such as maternal age, race, pre‐pregnancy BMI, parity, fertility treatment/method of conception, infant sex, and zygosity. The NICHD Fetal Growth Study was designed to assess foetal growth trajectories, foetal growth restriction, and maternal biomarkers of foetal growth in DCDA twins and compare these with singletons (2).…”
mentioning
confidence: 99%
See 3 more Smart Citations